A 5-DOF redundantly actuated parallel mechanism for large tilting five-face machining. (June 2022) - Yan, Peng; Huang, Hailin; Li, Bing; Zhou, Dunyi
Highlights: A novel 4PUS-PPPU redundantly actuated parallel mechanism is proposed. Large tilting movement is realized by using redundant actuation. Adaptive hybrid position/force control is proposed to reduce the internal force. The 4PUS-PPPU redundantly actuated parallel mechanism is fabricated. Abstract: This paper introduces the design, analysis, and control of a novel 5 degrees of freedom (DOFs) redundantly actuated parallel mechanism with a large tilting capacity. Firstly, a novel parallel mechanism consisting of four prismatic-universal-spherical (PUS) peripheral limbs and one special central prismatic-prismatic-prismatic-universal (PPPU) limb (4PUS-PPPU) is proposed. Secondary, analytical solution for the inverse kinematics of the proposed 4PUS-PPPU parallel mechanism is solved, singularity reduction by using a redundantly actuated central limb is analyzed, the workspace is also analyzed to show the perfect tilting capability of the proposed mechanism. Thirdly, computed-torque synchronization control is constructed to obtain the desired torque for each actuator when tracking a given trajectory. Fourthly, the adaptive hybrid position/force control strategy which is suitable for the redundantly actuated parallel mechanism is proposed to effectively adjust the internal force of the mechanism. Finally, a physical prototype is fabricated, the titling capacity and the effectiveness of the adaptive hybrid position/force control strategy are verified, polishing machining is employed as an example to demonstrate the performance of the proposed 4PUS-PPPU parallel mechanism.